The violence, the prisioner woman and the vulnerability to the STD/Aids - Giordani, Annecy T.; Bruno, Sonia M.V. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
We tried to investigate which the perception that the detentas has on the violence, detecting its problems and consequent infection risks for the HIVAIDS. We developed a research-action , humanist and qualitative, identifying with its wives relative problems the violence, working with them, later on, the intervention, using the methodology participativa. We everybody researched detentas (11), of that local. We used the individual interview, norteada for open subjects. The intervention through pedagogic shops. Front the sexual violence, everybody detests it revealing to have fear. Some revealed they have already been violentadas, resulting in deep traumas. As its experiences as victims, almost everybody raped e/ou was beaten. While victim of sexual violence, half almost refers to have been violentada for the boyfriend or uncle. Many revealed sorrow and fragility in this sense, affirming: I " felt very badly with that the wbole life ... , I feel not well even today only of thinking ", I am rioted with that ", " he made sex ... anal) with me, violently, it affected me too much ", I was " traumatizada tied ... mãos ... ". Some described that the reason that you/they took them to the jail, was the involvement with men that moved with drugs ... they still Highlight, the d isrespect that the soldiers have with them, a lot of times, being beating victims and of sexual violence, representing true menace for the infection of the DST / Aids. We concluded that the presented reports are loaded of trauma, inconformismo, rancor and he/she riots. They attribute to the unemployment and the poverty, indicative factors of violence, revealing conflicts and desolations to the they mention its experiences of sexual aggressions, exposing them to the risks of infection of DST and HIV/ Aids.